Cotrimoxazole reduces systemic inflammation in HIV infection by altering the gut microbiome and immune activation - Bourke, CD; Gough, EK; Pimundu, G; Shonhai, A; Berejena, C; Terry, L; Baumard, L; Choudhry, N; Karmali, Y; Bwarkura-Dangarembizi, M; Musiime, V; Lutaakome, J; et al. (American Association for the Advancement of Science, 2019)
Long-term cotrimoxazole prophylaxis reduces mortality and morbidity in HIV infection, but the mechanisms underlying these clinical benefits are unclear. Here, we investigate the impact of cotrimoxazole on systemic inflammation, an independent driver of HIV mortality. In HIV-positive Ugandan and Zimbabwean children receiving antiretroviral therapy, we show that plasma inflammatory markers were lower after randomization to continue (n = 144) versus stop (n = 149) cotrimoxazole. This was not explained by clinical illness, HIV progression, or nutritional status. Because subclinical enteropathogen carriage and enteropathy can drive systemic inflammation, we explored cotrimoxazole effects on the gut microbiome and intestinal inflammatory biomarkers. Although global microbiome composition was unchanged, viridans group Streptococci and streptococcal mevalonate pathway enzymes were lower among children continuing (n = 36) versus stopping (n = 36) cotrimoxazole. These changes were associated with lower fecal myeloperoxidase. To isolate direct effects of cotrimoxazole on immune activation from antibiotic effects, we established in vitro models of systemic and intestinal inflammation. In vitro cotrimoxazole had modest but consistent inhibitory effects on proinflammatory cytokine production by blood leukocytes from HIV-positive (n = 16) and HIV-negative (n = 8) UK adults and reduced IL-8 production by gut epithelial cell lines. Collectively we demonstrate that cotrimoxazole reduces systemic and intestinal inflammation both indirectly via antibiotic effects on the microbiome and directly by blunting immune and epithelial cell activation. Synergy between these pathways may explain the clinical benefits of cotrimoxazole despite high antimicrobial resistance, providing further rationale for extending coverage among people living with HIV in sub-Saharan Africa.